HIV-Positive Person - Marriage, Pregnancy and Perinatal / Vertical / Mother to Child Transmission: Awareness, Prevention and Recommendations - Bughio, Nasreen Inayat (Journal of Liaquat University of Medical & Health Sciences, 2025)
Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) is a global public health problem, with more than 40 million persons infected, and around 42 million persons have died from AIDS-related opportunistic infections to date. HIV transmission is ongoing in all countries.